2004
DOI: 10.1002/jso.20050
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity and expression of telomerase genes in squamous dysplasia and squamous cell carcinoma of the esophagus

Abstract: Higher telomerase activity and hTERT mRNA expression were shown during an early stage in the esophageal carcinogenesis. Activation of telomerase activity was strongly correlated with hTERT mRNA expression, suggesting hTERT is a major regulator of telomerase activity, and telomerase activation may play a critical role in esophageal carcinogenesis. Therefore, telomerase, especially hTERT can be used as a potential molecular biomarker of ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…ESCC has increased telomerase activity [91], but activation of telomerase is not related to prognosis in patients with ESCC [92]. …”
Section: The Gi Tract Cancers Telomeres and Telomere Maintenance Mementioning
confidence: 99%
“…ESCC has increased telomerase activity [91], but activation of telomerase is not related to prognosis in patients with ESCC [92]. …”
Section: The Gi Tract Cancers Telomeres and Telomere Maintenance Mementioning
confidence: 99%
“…Previously, telomerase activity has been identified in tumor initiating cells (3,18). Telomerase has been reported to be expressed in 86.2% esophageal carcinoma tissues; however, healthy esophageal tissue did not express it (19). Therefore, this suggests that there may be a window for telomerase inhibition-based treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent issue of the Journal of Surgical Oncology, Dr. Yu et al [1] report that increased telomerase activity was found in squamous dysplasia (44.7%) and carcinoma of the esophagus (86.2%), but not in normal esophageal tissue (0%). These data indicate that telomerase activation might play a role in esophageal carcinogenesis including the early pre-malignant dysplasia.…”
Section: Telomeres Arementioning
confidence: 99%